Trochleoplasty as a Solitary Treatment for Recurrent Patellar Dislocation Results in Good Clinical Outcome in Adolescents. (November 2016) - Camathias, Carlo; Studer, Katrin; Kiapour, Ata; Rutz, Erich; Vavken, Patrick
Background: The essential static patellar stabilizer is a normal-shaped trochlear groove. A dysplastic groove destabilizes the patella. Trochleoplasty approaches this underlying condition and reshapes the trochlea. However, studies have reported on trochleoplasty for revision cases or as accompanied by other interventions. The effect of trochleoplasty alone remains unexplained. Purpose: To introduce trochleoplasty as a stand-alone treatment for recurrent patellar dislocation and to compare its pre- to postoperative functional and clinical variables. Study Design: Case series; Level of evidence, 4. Methods: A trochleoplasty was performed in 50 knees (27 right) in 44 patients (30 females; mean ± SD age, 15.6 ± 2.0 years). The indication for surgery was recurrent patellar dislocation not responding to nonoperative treatment (>6 months), with types B through D dysplasia and closed or closing physes in adolescents aged 10 to 20 years. Assessment included J-sign and apprehension test, Kujala and Lysholm scores, patients' subjective assessment and activity level according to the International Knee Documentation Committee questionnaire, and patients' overall satisfaction. The Caton-Deschamps ratio and the lateral condyle index were measured. Pre- versus postoperative values were compared with a paired Wilcoxon signed-rank test. The minimum follow-up was 24 months (33 ± 10.6 months). Results: The Kujala score improved from 71 preoperatively to 92 postoperatively ( P < .001) and the Lysholm score from 71 to 95 ( P < .001). Patients' subjective assessment improved at the final follow-up as compared with that preoperatively ( P < .001). Most patients enhanced their activity ( P < .001), and their overall satisfaction increased postoperatively ( P < .001). Preoperatively, there was a positive J-sign in 45 knees and a positive apprehension test in 41 knees. Both markers disappeared postoperatively in 39 and 33 knees, respectively, leaving 6 knees with a positive J-sign and 8 knees with a positive apprehension test ( P < .001). One patella redislocated postoperatively after 38 months. Four patients required a single arthroscopic debridement. Conclusion: In this study, trochleoplasty as a solitary treatment for recurrent patellofemoral dislocations in patients with trochlear dysplasia resulted in good clinical outcomes if severe torsional and axial malalignment was excluded. Kujala and Lysholm scores increased postoperatively, as well as subjective International Knee Documentation Committee assessment of outcomes, activity level, and overall satisfaction.